Kuliner sebagai Kajian Budaya: Pindang Tetel dan Cerita Masyarakat Pekalongan - Aurelia Syaharani; Khaera Adinia Putri; Naeli Farkhah; Sekar Oktaviani; Sayidatim Milatina; Dimas Setiaji Prabowo (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
Pindang tetel is a traditional Pekalongan culinary specialty born from the creativity of the community in utilizing limited food ingredients, especially beef offal, which in the past was synonymous with lower-class consumption. This culinary dish not only serves as a daily meal, but also represents historical, social, and symbolic values ​​that reflect how Javanese people respond to their economic conditions and the dynamics of their lives. This study aims to examine the cultural meaning, local identity values, and the transformation process of pindang tetel in a modern context, especially when the dish is marketed in the tourist area of ​​Lake Al Kautsar, Kayugeritan. The study used a qualitative approach with a mini-ethnography method through direct observation, in-depth interviews with sellers, and informal conversations with consumers. The results show that pindang tetel has undergone adaptations in its presentation without losing its basic character, so it remains recognized as a traditional culinary dish. In the context of local tourism, pindang tetel serves as a representation of Pekalongan's cultural identity and a medium for cultural introduction for tourists. These findings confirm that traditional culinary plays an important role in shaping collective memory, strengthening local identity, and providing sustainable symbolic and social value in addition to economic value.